THE INFLUENCE OF PRACTICE METHOD AND ACHIEVEMENT MOTIVATION OF SHOT PUT SKILL - Ucok Hasian Refiater Ucok (Program Pascasarjana Universitas Negeri Jakarta, 2019)
The aim of this research is to find out influence of practice method and achievement motivation of shot put skill. It was done at Sport Major, Health and Sports Department of State University of Gorontalo. This research uses the experimental method with factorial design 2 x 2. The Population are 189 male students of Sport Major, though the sample which is used are 75 second-semester male students which passed the lecture of Athletic Shot put O’bryn which is divided into four groups, consists of 10 people each. Data Analysis uses the Variants Analysis (Anava) and Tukey Test for the next step. This Research concludes that: (1) There is a significant difference between plyometric and conventional practice method for Shot-Put skill. (2) For the High achievement motivation, plyometric practice method is better than the conventional practice method for the Shot-Put skill. (3) For those who have the lack of achievement motivation, there is no significant difference between plyometric and conventional practice method for the Shot Put skill. (4) There is positive interaction between practice method and achievement motivation for the shot put skill.